Studi Eksperimental Kinerja Putaran Mesin Kompos Penggerak Energi Konvensional dan Terbarukan - Wiradinata, Trisna Ardi; Asbanu, Husen; Esye, Yendi (Jurnal Sains & Teknologi Fakultas Teknik Universitas Darma Persada, 2025)
The availability of energy sources plays a vital role in supporting the efficiency of agricultural mechanisation, especially in the organic fertiliser processing process. This study evaluates and compares fertiliser processing machines' performance using two energy sources: a RON 90 fueled internal combustion engine and a 100 Wp solar power system. Testing was carried out at a fixed load of 3 kg with power and torque parameters observations. The results show that when using a 5.5 HP internal combustion engine, the increase in engine speed is directly proportional to the increase in power but inversely proportional to torque. The highest torque of 14.1 Nm is achieved at 1486 rpm with a power of 2.2 kW, while the highest power of 3.21 kW occurs at 2984 rpm with a torque decreasing to 10.2 Nm. On the other hand, the solar panel-based system showed an increase in power and torque as the intensity of sunlight increased, with the highest performance recorded at 1:00 PM at 91.8 watts and a torque of 0.30 Nm, which then decreased after 3:00 PM, indicating that the engine with a combustion engine has a more consistent performance. In contrast, the solar power system is highly dependent on daily fluctuations in light intensity, so it requires optimal operational time settings.